2007
DOI: 10.1080/08958370701260673
|View full text |Cite
|
Sign up to set email alerts
|

Smokers Have Reduced Nitric Oxide Production by Conducting Airways but Normal Levels in the Alveoli

Abstract: Air exhaled by cigarette smokers contains reduced amounts of nitric oxide (NO). Measurement of NO at different expiratory flow rates permits calculation of NO production by the conducting airways (Vaw(NO)) and alveolar concentration of NO (P(ALV)). An independent measurement of diffusing capacity of the alveolar compartment (D(LNO)) multiplied by P(ALV) allows calculation of NO production by the alveoli (V(LNO)). Twelve asymptomatic cigarette smokers and 22 age-matched nonsmokers had measurements of D(LNO) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…In accordance with the present findings, several studies have previously reported reduced FeNO levels in asthmatic smokers 10,26–28 . Reduction in FeNO may be attributed to (i) inhibition of nitric oxide synthase due to high concentrations of exogenous NO in cigarette smoke; (ii) increased levels of carbon monoxide in the airways of smokers, which also inhibits nitric oxide synthase; and (iii) the conversion of NO to peroxynitrite through reaction with other oxygen species or oxygen free radicals 29,30 . FeNO also did not differ significantly between asthmatic smokers and healthy smokers and this is in agreement with two previous studies 26,31 …”
Section: Discussionsupporting
confidence: 92%
“…In accordance with the present findings, several studies have previously reported reduced FeNO levels in asthmatic smokers 10,26–28 . Reduction in FeNO may be attributed to (i) inhibition of nitric oxide synthase due to high concentrations of exogenous NO in cigarette smoke; (ii) increased levels of carbon monoxide in the airways of smokers, which also inhibits nitric oxide synthase; and (iii) the conversion of NO to peroxynitrite through reaction with other oxygen species or oxygen free radicals 29,30 . FeNO also did not differ significantly between asthmatic smokers and healthy smokers and this is in agreement with two previous studies 26,31 …”
Section: Discussionsupporting
confidence: 92%
“…This decline may be associated with oxidant injury from the chemical milieu contained in tobacco smoke. Moreover, the persistent upregulation of CBF through an NO pathway may create a rich background for nitration of critical proteins with potentially pathogenic consequences (35). These studies document the immediate physiologic response of the airway epithelium to upregulate CBF upon exposure to tobacco smoke but more importantly suggest that that protracted exposures promote the persistence of this upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…The inducible NOS (iNOS) is transcriptionally regulated by pro-inflammatory cytokines in epithelial cells and macrophages in the airways (144). FeNO has been shown to be decreased by almost 50% in smokers in several cross-sectional studies (145148), possibly related to the large amount of NO in cigarette smoke (146). The reduction in FeNO also is thought to be related to nitric oxide synthase inhibition due to cigarette smoke carbon monoxide and/or oxygen free radicals (146, 149).…”
Section: Introductionmentioning
confidence: 99%
“…FeNO has been shown to be decreased by almost 50% in smokers in several cross-sectional studies (145148), possibly related to the large amount of NO in cigarette smoke (146). The reduction in FeNO also is thought to be related to nitric oxide synthase inhibition due to cigarette smoke carbon monoxide and/or oxygen free radicals (146, 149). Reduced FeNO has been reported to be significantly associated with increased neutrophilic inflammation (150).…”
Section: Introductionmentioning
confidence: 99%